Implementasi Undang-Undang No. 35 Tahun 2009 tentang Narkotika dalam Mencegah Penyalahgunaan Narkotika oleh Kalangan Mahasiswa di Provinsi Lampung : Studi Polda Lampung - Boby Pratama Jaya; Firganefi Firganefi; Dona Raisa Monica; Eko Raharjo; Refi Meidiantama (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
Drug abuse among university students is a serious phenomenon that affects the social, moral, and intellectual aspects of the younger generation. Students, who are ideally positioned as agents of change and drivers of national development, are often found to be vulnerable to drug abuse. This study aims to analyze the implementation of Law No. 35 of 2009 on Narcotics in preventing drug abuse among university students in Lampung Province, as well as to identify its inhibiting factors. The research employs a normative juridical and empirical juridical approach, using primary and secondary data obtained through interviews, field studies, and literature reviews. Key informants include the Narcotics Directorate of the Lampung Regional Police, P4GN Unila, the Vice-Rector III for Student Affairs and Alumni at Unila, and lecturers from the Criminal Law Department at Unila. The findings show that the Lampung Regional Police have implemented preventive strategies such as counseling, campaigns, urine tests, and drug abuse education on campuses, as well as repressive strategies through law enforcement against students involved in narcotics distribution, with 283 recorded cases over the past five years. However, the effectiveness of implementation is still hindered by limited campus facilities (counseling centers, safe reporting systems), the lack of regulatory responsiveness to digital challenges, and low student trust in law enforcement. Therefore, prevention efforts need to be strengthened through cross-sectoral synergy, policy updates, and the enhancement of the role of universities in creating a safe, healthy, and drug-free campus environment.